Where is the nursery for amphidromous nekton? Abundance and size comparisons of juvenile ayu among habitats and contexts. (31st August 2020) - Murase, Atsunobu; Ishimaru, Tetsuya; Ogata, Yukiya; Yamasaki, Yuta; Kawano, Hidenobu; Nakanishi, Kenji; Inoue, Kaito
Abstract: The use of estuarine and marine ecosystems by amphidromous fishes has not been thoroughly studied, especially with respect to habitat types. Here, abundance and size comparisons of juveniles of an amphidromous fish, ayu ( Plecoglossus altivelis altivelis ), were performed among four types of topographically distinct shallow, soft-bottom habitats across two different environmental contexts (marine and estuarine) through monthly seining along an estuary–ocean ecotone in southern Japan. Topography (open/enclosed and presence/absence of surf zone) and environmental parameters (water temperature and salinity) differed among the four habitats, i.e., riverine estuary, exposed beach, embayed beach, and lagoon estuary. The peak month of juvenile abundance also differed among habitats (riverine estuary in December, exposed beach in January, embayed beach and lagoon estuary in March), as did the mean standard length (riverine estuary < exposed beach < embayed beach < lagoon estuary), although the abundance at embayed beach was significantly greater than in the two estuaries, and almost all size classes of juveniles occurred at embayed beach. A likely explanation for these patterns is that juvenile ayu select coastal habitats as they develop swimming ability and that riverine estuary/exposed beach, embayed beach, and lagoon estuary function as a corridor, primary nursery, and possible foraging ground, respectively. These findings, coupled with implications from previous studies of habitat selection in coasts by anadromous fishes, highlight the importance of seascape-level analysis for elucidating the nursery functions of coastal habitats, even for diadromous nekton. Regional terms: North-western Pacific, East Asia, Japan, Kyushu, Miyazaki Prefecture. Graphical abstract: Image 1 Highlights: The use of coastal habitats by amphidromous fishes has been little studied. Abundance and size of juvenile ayu were compared among estuarine/marine habitats. Monthly abundance tended to be higher in one of the marine habitats. Juvenile size structure varied significantly among habitats. The results imply that amphidromous ayu exhibit nursery habitat selection.